Penyisihan Kadar Logam Cr (VI) Dan Cr (III) Pada Limbah Cair Elektroplating Dengan Kombinasi Proses Pengolahan Secara Biosorpsi Menggunakan Mikroalga Chlorella sp. Dan Koagulasi Flokulasi - Putri Sarah Nurliana Atmaja; Shinta Elystia; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Electroplating liquid wastewater is liquid wastewater that comes from the process of coating a metal with other metals with the help of an electric current. This research conducts processing of electroplating liquid wastewater using a combination of treatment processes by biosorption using microalgae Chlorella sp. immobilization in an airlift bioreactor and further processing by coagulation and flocculation in a coagulation and flocculation reactor using Poly Aluminum Chloride (PAC) coagulants. The purpose of this study was to determine the removal efficiency, initial concentration and optimum contact time and functional groups in microalgae Chlorella sp. The variation of treatment in this study is the initial concentration of wastewater of 25, 50, 75, 100% with variations in contact time for 1, 2, 3 and 4 days in the biosorption process and the addition of a coagulant dose of 600 mg / L in the flocculation coagulation process. The results showed that the biosorption process obtained the best variation in the concentration of 75% wastewater in 4 days contact time. The combination of biosorption, coagulation and flocculation processing can set aside the Cr (VI) content of 93.03% and Cr (III) of 69.8%. Keywords: Electroplating Liquid Wastewater, Chlorella sp., Chrom, Wastewater Concentration, Contact Time.